TECHNOLOGIES FOR DEVELOPING GENERAL AND FINE MOTOR SKILLS IN PRESCHOOL CHILDREN WITH DELAYED MENTAL DEVELOPMENT. (International journal of artificial intelligence, 2026)
This article deeply analyzes modern technologies and methodologies aimed at developing gross and fine motor skills in preschool children with delayed psychological development (DSPD). The study explores the psychological and pedagogical characteristics of DSPD, including the specific features of their motor development. The article thoroughly covers approaches such as using physical exercises, active games, and sports elements for improving gross motor skills, as well as finger games, sensory tools for developing fine motor skills. The importance of collaboration between families and specialists in evaluating the effectiveness of developmental technologies, as well as the role of person-centered and integrated approaches, is emphasized. The article concludes with practical recommendations and directions for future research.